ALIH KODE, CAMPUR KODE, DAN VARIASI BAHASA PADA PEMENTASAN WAYANG SASAK - Fendy Yogha Pratama; Cerianing Putri Pratiwi; Much. Nuril Huda (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2023)
The term Wayang Sasak refers to the puppet that developed and was staged in Lombok, West Nusa Tenggara. This study aims to describe the form of code mixing, code switching, and language variations in Sasak puppet performances. The source of the data was taken from the Sasak puppet performance with a play entitled "Sosialisasi Pencegahan Penularan Covid-19 di NTB" which was performed by dalang Lalu Nasib. This puppet performance is a form of socialization conducted by the Regional Secretariat of West Nusa Tenggara Province to provide education to the community. The results showed that the code switching and code mixing occurred in the performance. In addition, there are variations on ideolects, dialects and sociolects.